Covid-19 and Exposed to Vulnerabilities in The Creative Economy: Get Up Or Give Up - Agus Santosa; Rulinawaty Rulinawaty (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
Academic literature extensively acknowledges the fragile character of creative and cultural activity. However, it has frequently been invisible to policymakers and decision-makers. As soon as Covid-19 began affecting local and national economies worldwide, numerous business and policy organizations hastened to research the impact of Covid-19 on the creative and cultural industries (CCIs) and their workforce. The report provides insight into these organizations' primary issues through a meta-analysis of the current survey and research programs in the United Kingdom. The findings shed light on prevalent concerns regarding visible and unseen challenges that require attention in this area. The study continues by debating if Covid-19 represents a watershed event for the sector or merely reveals the unsustainable cost of creative and cultural activity.